Angiomatoid fibrous histiocytoma â an adolescent with an unusual presentation and course - Sara Isabel de Almeida; Sofia Cochito Sousa; Cristina Mendes; Rafael Cabrera; Ana Lacerda (Portuguese Journal of Pediatrics, 2025)
Introduction: Angiomatoid fibrous histiocytoma is a rare soft tissue neoplasm, which usually presents as an indolent mass in children and young adults and is often mistaken for a hematoma or hemangioma. Suspecting this diagnosis from imaging findings may be challenging, leading to diagnostic delays. Prognosis is generally favorable and metastases are infrequent at presentation. Case report: We describe the case of an adolescent who presented with a two-month history of a growing mass in the left scapular region, where diagnosis was made possible through surgical biopsy. Discussion: There were loco-regional lymphatic invasions and lung metastases at admission, and despite surgery and chemotherapy the disease rapidly progressed to death.